Kriteria Desain Pusat Rehabilitasi Down Syndrome Dengan Pendekatan Arsitektur Perilaku - Brenda Nathasya Siahaan; yunita Kesuma (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2021)
The result of Baseline Health Research through The Ministry of Health of the Republic of Indonesia showed that the number of down syndrome patients increased by 0,13% or approximately 300.000 cases in Indonesia. The Percentage of down syndrome cases was the second highest after physical disability cases, which always kept increasing. Down syndrome patients need an environment that is qualified to encourage society. This case has been an issue for the government to build a rehabilitation center in particular for the down syndrome patient in Indonesia, considering until this time, there are still no integrated rehabilitation centers that are qualified to provide not only academic activities but also medical therapies for the down syndrome patients. This study aimed to identify the condition of the physical elements that support learning methods for people with Down syndrome and to formulate the design criteria needed in a Down syndrome rehabilitation center. By using the behavior setting architecture approach expectantly able to provide the solution or criteria of the design for The Down Syndrome Rehabilitation Centre which is proper with the needs of down syndrome patients during their daily activities.